MARKET REACTIONS TO DOMESTIC MARKET OBLIGATION (DMO) COAL PRICE POLICY CHANGES: EVIDENCE FROM INDONESIA - Safitri, Titis Dyah; Maharani, Satia Nur; Narullia, Dwi (Jurnal Aplikasi Manajemen, 2021)
The announcement of the Domestic Market Obligation (DMO) coal price policy becomes the signal for investment decision making. The event was an announcement related to the government that can affect shares in the capital market. The form of capital market efficiency knows how equal the information that investors can absorb and the signal that indicates investors' response, whether it is positive or negative. This research is a descriptive event study that uses twenty-one samples of coal mining subsector companies to determine capital market reactions to the Domestic Market Obligation (DMO) coal price policy announcement. During the observation period, there was a significant market reaction with a marked abnormal negative return. There is a leak of information before implementing policy, which makes the form of capital market efficiency is semi-strong form. Also, this is caused by the investor, which gets the difference of information degree based on the market efficiency hypothesis. The next research can use different event windows to increase the knowledge about the effect of the announcement of the Domestic Market Obligation (DMO) coal price policy towards market reaction.